2007
DOI: 10.1007/s10832-007-9001-1
|View full text |Cite
|
Sign up to set email alerts
|

Domain wall contributions to the properties of piezoelectric thin films

Abstract: In bulk ferroelectric ceramics, extrinsic contributions associated with motion of domain walls and phase boundaries are a significant component of the measured dielectric and piezoelectric response. In thin films, the small grain sizes, substantial residual stresses, and the high concentration of point and line defects change the relative mobility of these boundaries. One of the consequences of this is that thin films typically act as hard piezoelectrics. This paper reviews the literature in this field, emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
223
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(241 citation statements)
references
References 83 publications
10
223
1
Order By: Relevance
“…Note that this approach has to be modified for polycrystalline ferroelectrics and especially capacitor based devices, where frequency dispersion can emerge as a result of domain wall dynamics within probing volumes. [337][338][339][340][341][342][343] However, the latter is usually reasonably weak (~<10%/decade).…”
Section: Via Means To Distinguish Piezoelectric From Non-piezoelectmentioning
confidence: 99%
“…Note that this approach has to be modified for polycrystalline ferroelectrics and especially capacitor based devices, where frequency dispersion can emerge as a result of domain wall dynamics within probing volumes. [337][338][339][340][341][342][343] However, the latter is usually reasonably weak (~<10%/decade).…”
Section: Via Means To Distinguish Piezoelectric From Non-piezoelectmentioning
confidence: 99%
“…In polycrystalline lead zirconate-titanate (PZT) ceramics, domain wall motion may contribute more than 50% of the dielectric and piezoelectric properties at room temperature [23,28]. However, in thin films these extrinsic contributions to the piezoelectric response can be severely limited by several factors, including substrate clamping [29]. Recent spatially resolved studies of piezoelectric nonlinearities have demonstrated the presence of micron-sized clusters of nonlinear activity, suggesting that surprisingly long-range phenomena are responsible for nonlinear interactions (at a length scale significantly larger than the grain size or domain size).…”
mentioning
confidence: 99%
“…Strong relaxation behavior is then observable for stronger positive and negative biases showing that the more heavily perturbed the domain state is (e.g., by applying higher biases), the easier it is to observe relaxation over the time scale investigated here. 89 To systematically explore the relaxation behavior in the (x,y,V) space, here we utilize the comparison in Eq. (4a) based on the analysis of variances (ANOVA) method.…”
Section: A Relaxation Dynamics Within Hysteresis Loopmentioning
confidence: 99%